Thermodynamics favoured preferential location of nanoparticles in co-continuous rubber blend toward improved electromagnetic properties. (July 2017) - Li, Lefan; Wang, Zhongqi; Zhao, Pengfei; Luo, Yongyue; Liao, Lusheng; Xu, Kui; Li, Puwang; Wang, Zhifen; Peng, Zheng
Graphical abstract: Highlights: Preferential nanofillers location in co-continuous rubber blend has been achieved. The obtained CB/NR/ENR composites show superior electromagnetic properties. Possible structure-property model is proposed to illustrated attenuation mechanism. Abstract: Engineered blend structure with tailor-made distribution of nanoparticles is the prime requisite to obtain materials with extraordinary functional properties. Here, preferential location of carbon black (CB) has been achieved in a binary elastomeric bend based on natural rubber (NR) and epoxidized natural rubber (ENR). Meticulous investigation has been conducted via thermodynamic, microscopic and electromagnetic analysis in order to illustrate the morphology-promoted performance behaviors. It is found that the filler-rubber interfacial tensions difference induces the preferential localization of CB in NR/ENR blend, thus endowing the composites with lower electrical percolation (2.11 vol.%), higher microwave absorption capacity (−19.31 dB) and broader effective absorption bandwidth (2.96 GHz). Such improved electromagnetic properties are ascribed to the higher conduction loss, stronger dielectric relaxation and more interface scattering of CB/NR/ENR composites.